2022
DOI: 10.3390/agronomy12112667
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Yield and Important Seed Quality Traits of Selected Legume Species

Abstract: Legumes are of great economic importance. Depending on the species, they are cultivated for food, fodder, green manure, and even as ornamentals. Legume seeds contain many valuable nutrients and also anti-nutritional substances. The aim of the study is to compare important seed quality traits in pea (Pisum sativum L.), faba bean (Vicia faba L.), white lupin (Lupinus albus L.), narrow-leafed lupin (Lupinus angustifolius L.), and yellow lupine (Lupinus luteus L.) to soybean (Glycine max (L.) Merr.). It was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Finally, K showed a very strong positive correlation with ash (0.94) and a very strong negative correlation with caloric value (−0.83), whereas P showed a strong negative correlation with carbohydrates (−0.72). A strong correlation between ash and K was also found for seeds of grain legumes [ 31 ].…”
Section: Resultsmentioning
confidence: 90%
“…Finally, K showed a very strong positive correlation with ash (0.94) and a very strong negative correlation with caloric value (−0.83), whereas P showed a strong negative correlation with carbohydrates (−0.72). A strong correlation between ash and K was also found for seeds of grain legumes [ 31 ].…”
Section: Resultsmentioning
confidence: 90%
“…Moreover, protein yield was strongly positively correlated with crude protein content in the seeds, while the relationship between seed yield and protein yield was weaker (r = 0.69). In contrast, Csajbók et al [30] noted that protein yield in soybeans was determined by seed yield rather than by protein content, while Jarecki et al [1] showed that seed yield was very strongly positively correlated with protein yield. Seed protein content was strongly negatively correlated with lipid content but was strongly positively correlated with K content and highly correlated with Mg content.…”
Section: Discussionmentioning
confidence: 95%
“…Legumes, depending on the species, are cultivated for food, fodder, green manure and even as ornamentals [1]. The introduction of post-harvest residues into the soil after legume cultivation determines the amount and timing of mineral forms of nitrogen, which are then available to subsequent crops [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the nutritional properties of these plants are now gaining in importance with regard to animal feeding. Most often, in a qualitative assessment of plants intended for food or fodder, after the verification of organic nutritional compounds, the contents of macro-and micronutrients are analysed (Struti et al, 2020;Jarecki and Migut, 2022). Unfortunately, the mutual relationships of nutrients are often overlooked and this aspect, according to Kumar and Soni (2014), should also be taken into consideration, because it directly determines the usefulness of fodder plants, and thus their impact on animal health.…”
Section: Discussionmentioning
confidence: 99%